1998
DOI: 10.1002/(sici)1097-461x(1998)70:6<1209::aid-qua10>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Optimal molecular connectivity descriptors for nitrogen‐containing molecules

Abstract: ABSTRACT:We report on optimal molecular connectivity descriptors for nitrogen atoms in amines for use in structure᎐property correlations. The descriptors represent generalized molecular connectivity indices with adjusted diagonal entries in the adjacency matrices of the corresponding molecular graphs, such that the standard error in a regression for boiling points in a set of amines is minimized. Advantages of the so-optimized descriptors for multivariate regression analysis in structure᎐property᎐ activity stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…This is quite an impressive improvement in the simple regression for the normal boiling points of smaller alcohols. Similar results were obtained when the normal boiling points of smaller amines were considered [34], when it was found that the standard error was reduced from 3.5°C when the connectivity index 1 χ was used, (that is when x = y = 0), to 1.9°C when x = 1.25 and y = -0.65. These two cases well illustrate the "power" of the variable connectivity index and suggest by extension that, in general, variable indices are likely to offer significant improvements in the regression analysis.…”
Section: Flexible Molecular Descriptorssupporting
confidence: 76%
“…This is quite an impressive improvement in the simple regression for the normal boiling points of smaller alcohols. Similar results were obtained when the normal boiling points of smaller amines were considered [34], when it was found that the standard error was reduced from 3.5°C when the connectivity index 1 χ was used, (that is when x = y = 0), to 1.9°C when x = 1.25 and y = -0.65. These two cases well illustrate the "power" of the variable connectivity index and suggest by extension that, in general, variable indices are likely to offer significant improvements in the regression analysis.…”
Section: Flexible Molecular Descriptorssupporting
confidence: 76%
“…There are several versions of the optimal (flexible) descriptors [11][12][13][14][15][16][17][18][19][20]. The present study is based on the only SMILES based optimal descriptor [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…The constructed augmented matrices are analogous to similar matrices that differentiate heteroatoms in molecules in the construction of the variable connectivity indices. [90][91][92][93][94][95][96][97][98][99][100][101][102][103] A similar approach of differentiation among proteomics maps associated with different drugs and other xenobiotic agents was used earlier in the literature on the mathematical characterization of proteomics maps using zigzag lines. [10,104] However, the normalizations used there were not adjusted to incorporate the dependence of matrix elements on the matrix size.…”
Section: Review Wwwq-chemorgmentioning
confidence: 99%
“…For better visibility of pairs of nucleotides that are aligned, blank spaces are added in-between. Table 22 shows that the first nucleotide pair GA appears at position 1 and at sites 7,11,38,43,89,101,110, and 112 in protein 1, and at the locations 1,5,7,11,37,42,54,64,69,88,100,109, and 113 in the second DNA. The two GA sets of (ordered) labels show that GA appears at the same locations Table 21.…”
Section: Rabhba : Gactcagaacccaccatgg mentioning
confidence: 99%